The Materiality of a Hybrid Capital in Partnerships on the Example of Limited Partnerships - Artur JASTRZEBOWSKI; Marek WIERZBINSKI (Communications of International Proceedings, 2020)
This article aims to present arguments that justify the introduction of hybrid capital in limited partnerships’ financial statements. A limited partnership is becoming an increasingly popular form of doing business. Legal regulations in the field of accounting, as well as the literature, do not devote sufficient attention to limited partnerships or other partnerships. Issues connected with, among others, the recognition gap in accounting books and the presentation of equity in the financial statement. One of the tools which can help to cover it is hybrid capital. The work was prepared with the use of literature analysis methods and Polish regulations regarding the functioning of companies. A detailed analysis of statistical data was made in the empirical part. As a result of the research, the significance of the information gap in the area of an entity's capital was identified, and thus the potential for using the hybrid capital presentation was demonstrated.
Keywords: Materiality Principle; Limited Partnership Company; Hybrid Capital; Accounting of Limited Partnership Company.